Silencing of the sulfur rich α-gliadin storage protein family in wheat grains (Triticum aestivum L.) causes no unintended side-effects on other metabolites - Zörb, Christian; Becker, Dirk; Hasler, Mario; Muehling, Karl H.; Gödde, Victoria; Niehaus, Karsten; Geilfus, Christoph M. (Frontiers in Plant Science, 2013)
Wheat is an important source of proteins and metabolites for human and animal nutrition. To assess the nutritional quality of wheat products, various protein and diverse metabolites have to be evaluated. The grain storage protein family of the α-gliadins are suggested to be the primary initiator of the inflammatory response to gluten in Celiac disease patients. With the technique of RNAi, the α-gliadin storage protein fraction in wheat grains was recently knocked down. From a patient's perspective, this is a desired approach, however, this study aims to evaluate whether such a down-regulation of these problematic α-gliadins also has unintended side-effects on other plant metabolites. Such uncontrolled and unkown arbitrary effects on any metabolite in plants designated for food production would surely represent an avoidable risk for the consumer. In general, α-gliadins are rich in sulphur, making their synthesis and content depended of the sulphur supply. For this reason, the influence of the application of increasing sulphur amounts on the metabolome of α-gliadin-deficient wheat was additionally investigated because it might be possible that e.g. considerable high/low amounts of S might increase or even induce such unintended effects that are not observable under moderate S nutrition. By silencing the α-gliadin genes, a recently developed wheat line that lacks the set of 75 corresponding α-gliadin proteins has become available. The plants were subsequently tested for RNAi-induced effects on metabolites that were not directly attributable to the specific effects of the RNAi-approach on the α-gliadin proteins. For this, GC-MS-based metabolite profiles were recorded. A comparison of wild type with gliadin-deficient plants cultivated in pot experiments revealed no differences in all 109 analyzed metabolites, regardless of the S-nutritional status. No unintended effects attributable to the RNAi-based specific genetic deletion of a storage protein fraction were observed.